2016
DOI: 10.1103/physreva.94.043636
|View full text |Cite
|
Sign up to set email alerts
|

Universal one-dimensional atomic gases near odd-wave resonance

Abstract: We show the renormalization of contact interaction for odd-wave scattering in one-dimension(1D). Based on the renormalized interaction, we exactly solve the two-body problem in a harmonic trap, and further explore the universal properties of spin-polarized fermions near odd-wave resonance using the operator product expansion method. It is found that the high-momentum distribution behaves as C/k 2 , with C the odd-wave contact. Various universal relations are derived. Our work suggests a new universal system em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…In the presence of SO coupling, only s-and p-wave scatterings are involved in the subspace K = 0 and J = 0, and the wave function at short distance takes the form of Eq. (25). Using the asymptotic behavior of the wave function, we easily evaluatê…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of SO coupling, only s-and p-wave scatterings are involved in the subspace K = 0 and J = 0, and the wave function at short distance takes the form of Eq. (25). Using the asymptotic behavior of the wave function, we easily evaluatê…”
Section: Discussionmentioning
confidence: 99%
“…All these relations are characterized by the only universal quantity named contact, and therefore known as the contact theory. During past few years, the concept of contact theory was further generalized to higher-partial-wave interactions [13][14][15][16][17][18][19][20] as well as to low dimensions [21][22][23][24][25][26][27][28][29], and more contacts appear when additional two-body parameters are involved.…”
Section: Introductionmentioning
confidence: 99%
“…This interesting mapping was pointed out also directly in a very pedagogical paper [345], where the exact analytical solution (counterpart of the Busch et. al solution) for the two-particle problem with p-wave interactions in a harmonic trap was obtained (see also [348] for the solution obtained with different method). Based on this solution, in [349] the first analysis of inter-particle quantum correlations in the interacting two-body ground state was studied and compared with those induced by s-wave interactions.…”
Section: A Beyond S-wave Interactionsmentioning
confidence: 99%
“…Experimentally, a major obstacle for exploring p-wave effect in cold atoms is the severe atom loss, as observed in a 3D Fermi gas [26][27][28][29]. Recent studies have suggested that the p-wave system could be more stable against three-body loss if confined in the quasi-1D geometry [30,31]. In our system, an additional optical lattice is applied along the 1D tube and the space is further discretized.…”
Section: Introductionmentioning
confidence: 99%